High-mass X-ray binaries in nearby metal-poor galaxies: on the contribution to nebular He ii emission. Issue 1 (28th February 2020) - Senchyna, Peter; Stark, Daniel P; Mirocha, Jordan; Reines, Amy E; Charlot, Stéphane; Jones, Tucker; Mulchaey, John S
ABSTRACT: Despite significant progress both observationally and theoretically, the origin of high-ionization nebular He ii emission in galaxies dominated by stellar photoionization remains unclear. Accretion-powered radiation from high-mass X-ray binaries (HMXBs) is still one of the leading proposed explanations for the missing He + -ionizing photons, but this scenario has yet to be conclusively tested. In this paper, we present nebular line predictions from a grid of photoionization models with input spectral energy distributions containing the joint contribution of both stellar atmospheres and a multicolour disc model for HMXBs. This grid demonstrates that HMXBs are inefficient producers of the photons necessary to power He ii, and can only boost this line substantially in galaxies with HMXB populations large enough to power X-ray luminosities of 10 42 erg s −1 per unit star formation rate (SFR). To test this, we assemble a sample of 11 low-redshift star-forming galaxies with high-quality constraints on both X-ray emission from Chandra and He ii emission from deep optical spectra, including new observations with the MMT. These data reveal that the HMXB populations of these nearby systems are insufficient to account for the observed He ii strengths, with typical X-ray luminosities or upper limits thereon of only 10 40 –10 41 erg s −1 per SFR. This indicates that HMXBs are not the dominant source of He + ionization in these metal-poor star-forming galaxies. We suggest that the solution may instead reside in revisions to stellar wind predictions, softer X-ray sources, or very hot products of binary evolution at low metallicity.